2019
DOI: 10.1016/j.actamat.2019.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation and hardening in irradiated low alloy steels with a wide range of Ni and Mn compositions

Abstract: Mn-Ni-Si intermetallic precipitates (MNSPs) that are observed in some Fe-based alloys following thermal aging and irradiation are of considerable scientific and technical interest. For example, large volume fractions (f) of MNSPs form in reactor pressure vessel low alloy steels irradiated to high fluence, resulting in severe hardening induced embrittlement. Nine compositionally-tailored small heats of low Cu RPV-type steels, with an unusually wide range of dissolved Mn (0.06-1.34 at.%) and Ni (0.19-3.50 at.%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
38
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 49 publications
(95 reference statements)
8
38
1
Order By: Relevance
“…Thus, CPI were used here to characterize precipitation for a matrix of advanced alloys with compositions that extend beyond the typical range the current RPV steels. The focus is on developing so-called super-clean steels, with very high Ni contents (> 3 wt.%), that have superior unirradiated properties [11][12][13][14][15][16]. However, high Ni levels lead to 4 enormous irradiation hardening and embrittlement in RPV steels with typical Mn and Si contents [11].…”
Section: Introduction Background and Objectivementioning
confidence: 99%
“…Thus, CPI were used here to characterize precipitation for a matrix of advanced alloys with compositions that extend beyond the typical range the current RPV steels. The focus is on developing so-called super-clean steels, with very high Ni contents (> 3 wt.%), that have superior unirradiated properties [11][12][13][14][15][16]. However, high Ni levels lead to 4 enormous irradiation hardening and embrittlement in RPV steels with typical Mn and Si contents [11].…”
Section: Introduction Background and Objectivementioning
confidence: 99%
“…The underprediction of embrittlement at high fluence is primarily attributed to the delayed formation of large volume fractions (f) of Mn-Ni-Si precipitates (MNSPs), which are not accounted for in current regulatory models [4][5][6][7][8]. The existence of MNSPs has been demonstrated in both surveillance and test reactor irradiations [4,[9][10][11][12][13][14][15][16][17][18][19][20][21][22], but their detailed character and formation mechanisms is one of the most highly debated issues in the field of radiation effects [4,14,[23][24][25][26]. The central question relates to the driving force for MNSP formation.…”
mentioning
confidence: 99%
“…Note, even if it is shown that the MNSPs are stable, and the driving force for forming MNSPs is largely thermodynamic, RIS may affect the precipitate compositions somewhat [11]. Indeed, it is important to emphasize that RIS and RED work in tandem, and both can and do play a role in MNSP evolution in RPV and other steels.…”
mentioning
confidence: 99%
“…The multicomponent alloys including Ti-base [1], Nibase [2,3], Fe-base [4], Al-base [5], and high entropy alloys [6], are composed of five or more metallic elements, which makes it increasingly complex to study the relationships among composition, phases, process, and properties. For example, the Ni-base superalloys, used for turbine blades and disks, generally contain over eight alloying elements, the phase precipitation and mechanical properties are found very sensitive to the composition variation [3,7].…”
Section: Introductionmentioning
confidence: 99%